DYNAMICS OF THE IMPACT OF NEUROPSYCHOLOGICAL RESILIENCE ON BEHAVIOURAL DEVIATIONS IN MILITARY PERSONNEL DURING THEIR PROFESSIONAL DEVELOPMENT - Safin, Oleksandr; Mas, Nataliia; Teptyuk, Yuliia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . Military service is characterised by high levels of physical and psychological strain, which can reach critical thresholds during combat operations. This may result in maladaptive and deviant forms of behaviour in military personnel encountering such stressors for the first time. The process of professional development in military personnel (professiogenesis) involves, among other aspects, the formation of a strong moral and spiritual core, which acts as a safeguard against the emergence of deviant behaviour. However, military service is inherently saturated with stress, and over time, cumulative stress may increase the risk of behavioural deviations.M e t h o d s . The following psychodiagnostic tools and methods were employed: V. Mendelevych's scales for addiction-prone behaviour ("Tendency toward drug dependence", "Tendency toward alcohol dependence"); the Delinquent and Addictive Behaviour Questionnaire (DAP-2); scales assessing "Tendency toward deviant forms of behaviour", "Military-professional orientation", "Addictiveness", "Delinquency", "Suicidal risk", and "Number of evasive responses"; the SANT-30 diagnostic system (including: "Tendency toward suicidal reactions", "Risk of unauthorised use of weapons against others", "Tendency toward drug and substance abuse"); Early Signs of Alcoholism Questionnaire; Bass-Perry Aggression Questionnaire (BPAQ-24) with subscales: "Physical aggression", "Anger", "Hostility", "Overall aggression index"; and statistical methods including mean values, standard deviation, Spearman's rank correlation, Mann–Whitney U-test, Kruskal–Wallis test, and factor analysis.R e s u l t s . The hypothesis was confirmed that there are measurable differences in the manifestation of deviant behavioural tendencies among military personnel of different categories. The study of deviant behaviour across military categories enables the collection of data necessary for the development of a targeted prevention programme. Preventing the emergence of behavioural deviations requires consistent psychological education, as well as psychological screening and ongoing support of military personnel.C o n c l u s i o n s . To prevent the development of deviant behaviour among military personnel, appropriate preventive measures must be implemented, particularly focusing on the risks of drug dependency and suicidal tendencies. Additional psychological education and training for officers are necessary to equip them with the skills to detect and respond to early signs of deviant behaviour. Furthermore, officers and military psychologists must maintain a unit climate conducive to discipline and morale, which in turn reduces the risk of behavioural deviations and supports sustained professional orientation. A low level of motivation to fulfil military duties is itself a risk factor in the development of such behaviours.
Keywords: physical and psychological stress, maladaptive and deviant behaviour, professiogenesis, deviations, stress, professional orientation